Coordinated Support of Stakeholders in the Manufacturing Sector in Ethiopia; Challenges and Solutions - Gebresilassie, Kiros Haftetsion (Journal of Social Sciences and Management Studies, 2023)
The primary objective of this study is to explore the current situation of stakeholders’ coordination in supporting the manufacturing sector and the challenges they face in supporting the sector in a coordinated approach as required. The study employed more of a qualitative approach whereas the quantitative approach has been used slightly. Therefore, the study was done by collecting mainly primary data by interviewing key informant officials and investors as well as questionnaires were developed to collect primary data from government stakeholders and investors. In addition, secondary data was also used as a source of information for the study. The results of the study show that, at this time the stakeholders who support the sector have no coordinated system. As an indicator, they do not have a signed document or procedure to work together. Furthermore, there is no single window/one service center to support the sector together with the stakeholders. In addition, lack of foreign currency supply, lack of developed working place, infrastructure and power interruptions, bureaucracy and rent-seeking behaviour, and procedures of revenue and customs are the biggest obstacles to investors in the sector